Language Attitude of Teenagers Towards Buru Language in the Coastal Communities of Buru Regency - Azwan Azwan; Sitti Hajiyanti Makatita (Interference: Journal of Language, Literature, and Linguistics, 2022)
This research aimed to find out the language attitude of teenagers towards Buru language in the coastal communities of Buru regency. This research was descriptive by quantitative and qualitative approaches. This research was conducted in Buru Regency, with a population of coastal communities. There were 80 teenagers from each subdistrict as the samples. The technique of collecting data was through the questions list in the questionnaire instrument. The result of this research showed that the language attitude of teenagers towards the Buru language in the coastal community of Buru Regency tends to be negative. They have good attitudes in cognitive aspects but differed in affective and conative aspects. It can be seen in the results of the average index value generated for the Buru language was 2.39 in a non-positive category. Internal and external factors were triggers for the language attitude of teenagers. Internal factors came from teenagers who did not feel proud of their mother tongue, whereas external factors were influenced by family environment, daily interactions, and educational environment.